Analysis of Risk Management Practices among Maize Based Farmers in Abia State, Nigeria - O.O, Nto Philips (Asian Economic and Financial Review, 2016)
The study analyzed risk management practices among maize based farmers in Abia State of Nigeria. The specific objectives included (a) the Categorization of input variables associated with risk in maize farming into factors; (b) determination of the level of influence of loaded variables on risk and (c) examination of risk reducing practices adopted by maize farmers in the area. Multistage sampling technique was adopted in selecting 120 maize based farmers from three zones in the study area. Well-structured and pretested questionnaires were used in the collection of data. The data were analyzed using factor analysis, censored regression analysis and descriptive statistics. The result of the censored regression analysis indicates that variables like diseases and pests, invasion by cow, policy inconsistency and lack of improved varieties were positively significant at various probability levels. It was recommended that government should ensure availability of improved varieties and pesticides at subsidized rate as well as provide paddock for cow grazing. Farmers were also encouraged to adopt measures that will reduce cow invasion like fencing of farmland.